Ceramide synthesis regulates T cell activity and GVHD development - M. Hanief Sofi; Jessica Heinrichs; Mohammed Dany; Hung Nguyen; Min Dai; David Bastian; Steven Schutt; Yongxia Wu; Anusara Daenthanasanmak; Salih Gencer; Aleksandra Zivkovic; Zdzislaw Szulc; et al. (JCI Insight, 2017)
Allogeneic hematopoietic cell transplantation (allo-HCT) is an effective immunotherapy for a variety of hematologic malignances, yet its efficacy is impeded by the development of graft-versus-host disease (GVHD). GVHD is characterized by activation, expansion, cytokine production, and migration of alloreactive donor T cells. Hence, strategies to limit GVHD are highly desirable. Ceramides are known to contribute to inflammation and autoimmunity. However, their involvement in T-cell responses to alloantigens is undefined. In the current study, we specifically characterized the role of ceramide synthase 6 (CerS6) after allo-HCT using genetic and pharmacologic approaches. We found that CerS6 was required for optimal T cell activation, proliferation, and cytokine production in response to alloantigen and for subsequent induction of GVHD. However, CerS6 was partially dispensable for the T cell–mediated antileukemia effect. At the molecular level, CerS6 was required for efficient TCR signal transduction, including tyrosine phosphorylation, ZAP-70 activation, and PKCθ/TCR colocalization. Impaired generation of C16-ceramide was responsible for diminished allogeneic T cell responses. Furthermore, targeting CerS6 using a specific inhibitor significantly reduced T cell activation in mouse and human T cells in vitro. Our study provides a rationale for targeting CerS6 to control GVHD, which would enhance the efficacy of allo-HCT as an immunotherapy for hematologic malignancies in the clinic.